Disposition of Hexahydrocannabinol Epimers and Their Metabolites in Biological Matrices following a Single Administration of Smoked Hexahydrocannabinol: A Preliminary Study - Di Trana, Annagiulia; Di Giorgi, Alessandro; Sprega, Giorgia; Carlier, Jeremy; Kobidze, Giorgi; Montanari, Eva; Taoussi, Omayema; Bambagiotti, Giulia; Fede, Maria Sofia; Lo Faro, Alfredo Fabrizio; Tini, Anastasio; Busardò, Francesco Paolo; et al. (Pharmaceuticals (Basel, Switzerland), 2024)
In 2023, hexahydrocannabinol (HHC) attracted the attention of international agencies due to its rapid spread in the illegal market. Although it was discovered in 1940, less is known about the pharmacology of its two naturally occurring epimers, 9(R)-HHC and 9(S)-HHC. Thus, we aimed to investigate the disposition of hexahydrocannabinol epimers and their metabolites in whole blood, urine and oral fluid following a single controlled administration of a 50:50 mixture of 9(R)-HHC and 9(S)-HHC smoked with tobacco. To this end, six non-user volunteers smoked 25 mg of the HHC mixture in 500 mg of tobacco. Blood and oral fluid were sampled at different time points up to 3 h after the intake, while urine was collected between 0 and 2 h and between 2 and 6 h. The samples were analyzed with a validated HPLC-MS/MS method to quantify 9(R)-HHC, 9(S)-HHC and eight metabolites. 9(R)-HHC showed the highest Cmax and AUC0–3h in all the investigated matrices, with an average concentration 3-fold higher than that of 9(S)-HHC. In oral fluid, no metabolites were detected, while they were observed as glucuronides in urine and blood, but with different profiles. Indeed, 11nor-9(R)-HHC was the most abundant metabolite in blood, while 8(R)OH-9(R) HHC was the most prevalent in urine. Interestingly, 11nor 9(S) COOH HHC was detected only in blood, whereas 8(S)OH-9(S) HHC was detected only in urine.